2008
DOI: 10.2478/v10032-008-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Colour of Light on Cucumber (Cucumis Sativus L.) Seedlings

Abstract: Cucumber productivity can be optimize by regulating their photoperiod. Photoperiod will affect the production of female flower, the basis for the production of cucumber fruit. In this research, two cucumber lines (Mercy and KE 27187) was treated with 8, 12, and 16 hours of light by using red light (λ red = 630 nm), blue light (λ blue = 460 nm), and yellow light (λ yellow = 510 nm) LEDs. Treatment from 12 h of light increased sugar accumulation (7482, 69 ppm) but not too different compared to 8 hours and 16 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…(Glowacka, 2006). Blue light can increase or decrease shoot and internode lengths, shoot dry matter, as well as leaf area (Abidi et al, 2013;Brown et al, 1995;Glowacka, 2004;Hernández and Kubota, 2014;Ohashi-Kaneko et al, 2007;Piszczek and Głowacka, 2008;Wilson et al, 1993) (Table 1). In some species, it has no …”
Section: Consequences Of Uv and Blue Light Perception On Plant Vegetamentioning
confidence: 98%
“…(Glowacka, 2006). Blue light can increase or decrease shoot and internode lengths, shoot dry matter, as well as leaf area (Abidi et al, 2013;Brown et al, 1995;Glowacka, 2004;Hernández and Kubota, 2014;Ohashi-Kaneko et al, 2007;Piszczek and Głowacka, 2008;Wilson et al, 1993) (Table 1). In some species, it has no …”
Section: Consequences Of Uv and Blue Light Perception On Plant Vegetamentioning
confidence: 98%
“…Similarly, shoot elongation is increased under blue light in pepper (Brown et al. 1995) and cucumber (Piszczek & Glowacka 2008), whereas it is repressed in Pinus (Sarala et al. 2007) and in S. tuberosum (Wilson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Also there are few studies describing effect of solar conditions on growth, development and yield of cucumber (Liebig, 1985;Liebig and Krug, 1991;Kharkina et al, 2003;Ibarra-Jiménez et al, 2008;Kalbarczyk, 2009), but there are a lot more studies devoted to optimization of cultivation and cropping physiology of the characterized plant (Peil and López-Gálvez, 2002;Talanov et al, 2005;Piszczek and Glowacka, 2008). Cucumber ontogenesis, from seed germination to final stages of ageing and their death, is controlled by light.…”
Section: Discussionmentioning
confidence: 99%
“…According to these researchers optimal light and thermal conditions are: day duration amounting to 13 h, light intensity -130 klx and average temperature -30ºC. Piszczek and Glowacka (2008) evaluated the effect of the colour of light on cucumber planting and found that cucumber plants growing under lamps with blue light, compared with daylight, were higher, had longer internodes, a thicker stem and a higher content of dry mass in the fresh mass of shoots. According to Piszczek and Glowacka (2008), with quantum irradiation of intensity amounting to 60 μmol m -2 s -1 the content of chlorophyll and carotenoids was bigger in the leaves of plants growing in daylight and the content of anthocyanins was not reliant on the colour of light and the intensity level of quantum irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation